Field Demonstration of the Horizontal Treatment Well (HRX Well®) for Passive In Situ Remediation. Issue 3 (7th August 2020) - Divine, Craig E.; Wright, Jesse; Crimi, Michelle; Devlin, J.F.; Lubrecht, Michael; Wang, Jack; McDonough, Jeff; Kladias, Michael; Hinkle, Jesse; Cormican, Allison; Osorno, Trevor; Nzeribe, Blossom N.; et al.
Abstract: The horizontal reactive media treatment well (HRX Well®) uses directionally drilled horizontal wells filled with a treatment media to induce flow‐focusing behavior created by the well‐to‐aquifer permeability contrast to passively capture proportionally large volumes of groundwater. Groundwater is treated in situ as it flows through the HRX Well and downgradient portions of the aquifer are cleaned via elution as these zones are flushed with clean water discharging from the HRX Well. The HRX Well concept is particularly well suited for sites where long‐term mass discharge control is a primary performance objective. This concept is appropriate for recalcitrant and difficult‐to‐treat constituents, including chlorinated solvents, per‐ and polyfluoroalkyl substances (PFAS), 1, 4‐dioxane, and metals. A full‐scale HRX Well was installed and operated to treat trichloroethene (TCE) with zero valent iron (ZVI). The model‐predicted enhanced flow through the HRX Well (compared to the flow in and equivalent cross‐sectional area orthogonal to flow in the natural formation before HRX Well installation) and treatment zone width was consistent with flows and widths estimated independently by point velocity probe (PVP) testing, HRX Well tracer testing, and observed treatment in downgradient monitoring wells. The actual average capture zone width was estimated to be between 45 and 69 feet. Total TCE mass discharge reduction was maintained through the duration of the performance monitoring period and exceeded 99.99% (%). Decreases in TCE concentrations were observed at all four downgradient monitoring wells within the treatment zone (ranging from 50 to 74% at day 436), and the first arrival of treated water was consistent with model predictions. The field demonstration confirmed the HRX Well technology is best suited for long‐term mass discharge control, can be installed under active infrastructure, requires limited ongoing operation and maintenance, and has low life cycle energy and water requirements. Abstract : Article impact statement : The HRX Well® is a new type of permeable reactive barrier technology that passively captures and treats a wide range of groundwater contaminants in situ.